The Influences of Inquiry Learning Model with Scaffolding on Scientific Literacy and Learning Outcomes - Hamidah, Luluk Nur; Koeshandayanto, Supriyono; Mashfufah, Aynin (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2024)
The purpose of this study is to analyze the significant effect of the inquiry model with scaffolding on science literacy and science learning outcomes. This type of research uses quasi-experimental and quantitative methods with a non-equivalent posttest-only control class design. The sample was determined using the class random sampling technique within abstract groups with a random technique, and the study population was all 6th-grade students in Cluster II of Blitar Regency. This study used a sample of 48 6th-grade students in the control class of 26 students and 21 students in the experimental class, selected using a random sampling technique. The sample selection criteria were based on students who showed variations in science literacy based on the results of initial observations and discussions with class teachers. The study was conducted in the even semester of the 2023/2024 academic year. Data collection was carried out using tests. The data in this study consisted of quantitative and qualitative data. Quantitative data in the form of student test scores. Qualitative data were obtained through interviews with class teachers and open questionnaires for 6th-grade students. Data collection methods include observations of student learning activities in class, structured interviews with teachers, and document analysis of students' science literacy scores at school. The data were analyzed using statistical tests Anova and Manova. The results showed that the use of inquiry models with scaffolding had a positive effect on the scientific literacy of grade 6 students (the F count of 4.841 is greater than the F table of 4.05), which is equal to 29.742, which is greater than the F table of 4.05). Simultaneously, there is an effect between scientific literacy and the science learning outcomes of students taught using the inquiry scaffolding model, obtained F of 29.0742; p less than 0.05. It is concluded that the use of inquiry models with scaffolding contributes to improving scientific literacy and science learning outcomes.